2021
DOI: 10.3389/fpsyg.2020.544661
|View full text |Cite
|
Sign up to set email alerts
|

My Future: Psychodrama and Meditation to Improve Well-Being Through the Elaboration of Traumatic Loss Among Italian High School Students

Abstract: This study was designed as an action research aimed to help students to elaborate their feelings of traumatic grief, due to a car accident and a suicide of two of their classmates, in an Italian high school. A death education project was realized in order to prevent the Werther effect. The intervention was based on psychodramatic techniques and meditation with Tibetan bells to encourage reflection on the suffering of traumatic loss, the sense of life, and their future. A total of 89 students from four classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is also noted that the results suggested that drama-based intervention was beneficial but not statistically significant for enhancing psychological well-being. For example, a psychodrama programme improved the psychological balance of adolescents who had experienced a traumatic incident; the correlations showed increased psychological progress [ 71 ]. Furthermore, the results may point to the potential role of drama-based intervention in improving communication skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noted that the results suggested that drama-based intervention was beneficial but not statistically significant for enhancing psychological well-being. For example, a psychodrama programme improved the psychological balance of adolescents who had experienced a traumatic incident; the correlations showed increased psychological progress [ 71 ]. Furthermore, the results may point to the potential role of drama-based intervention in improving communication skills.…”
Section: Discussionmentioning
confidence: 99%
“… Risk of bias summary for each included study [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. …”
Section: Figurementioning
confidence: 99%
“…Since this research was carried out before the outbreak of the Covid-19 pandemic, future research might explore if and how the pandemic and the consequent changes it brought about might have influenced college students' narratives in regard of their reasons for living and for dying and on potential resources for suicide prevention interventions. To conclude, Death Education in the form of education on suicide prevention can offer young people a space in which to ponder on theirs and their peers' reasons for living and dying and to create their personal narrative on the meaning life has for them [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The need for such spaces stems from the changes brought about by the postmodern era, such as a great increase in well-being and the secularization of society with the consequent removal of any form of reflection upon death and human limits [14]. The awareness of finitude, in turn, makes humans appreciate their time spent on Earth, thus valorizing life and strengthening their will to safeguard it [7,15]. DeEd is aimed at creating an appropriate language around death and death-related issues, creating a space to recognize, experience and share emotions and feelings derived by thinking about death, reasoning on human limits and finitude and on the meaning of life, to reduce death anxiety and create a safe space for students to share their learning experiences, together with their thoughts and feelings [16].…”
Section: Introduction 1death Education As Education On Suicide Preventionmentioning
confidence: 99%
“…Such self-representation allows individuals to maintain the cultural framework through which meaning is given to everyday life [21]. In fact, giving life meaning and conceiving death as a passage are factors that have been closely linked to lower levels of distress, anxiety, and depression [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%